Predictors affecting vaccine hesitancy towards annual COVID-19 booster shots among populations from different countries - Sylvana Nady Gaber; Wafaa Y. Abdel Wahed; Bismark Jampim Abrokwah; Mohammed Ibrahim Al Hawamdeh; Lubna Abdelwahab Elsidigg; Ahmed A. Wegdan; Rasha H. Bassyouni (BMC Public Health)
Abstract Background Coronavirus Disease-19 (COVID-19) is reported to cause significant mortalities. Vaccination has the probability to reduce the burden of COVID-19. Annual vaccination is better to be established, but vaccine reluctance has been observed among different populations. Objectives To recognize the associated factors and the predictors affecting vaccine hesitancy towards annual COVID-19 vaccine shots among African and Asian populations. Method A cross-sectional study was conducted on a population from diverse nationalities using a structured, self-administered questionnaire. Adjusted odds ratios (ORs) and their 95% confidence intervals (CIs) were estimated using multiple logistic regression to identify predictors of vaccine hesitancy. Results A total of 502 participants from four countries: 152 Jordanians (30.3%), 145 Egyptians (28.9%), 103 Ghanaians (20.5%), and 102 Sudanese (20.3%) were included in the study. The majority were females (307, 61.2%). Egyptians show the highest willingness to receive annual COVID-19 vaccine shots (99, 68.3%), while Jordanians (68, 44.7%), Ghanaians (42, 40.8%), and Sudanese (60, 58.8%) exhibit more hesitancy or refusal. Hesitancy is higher among the younger age group (56.5%, P = 0.003) and lower education levels (55.6%, P = 0.008). Higher knowledge (OR = 0.843, p = 0.002), and a positive attitude toward vaccine administration (OR = 0.878, P < 0.001) significantly predict lower hesitancy. The fear of severe side effects (42%) was the most common cause of COVID-19 vaccine hesitancy. Conclusions Young age and low education levels are linked with increased hesitancy toward annual COVID-19 vaccination shots. Higher knowledge, and positive attitude, and previous influenza vaccination predict annual vaccine hesitance. Public health actions in the form of awareness campaigns are needed to promote the importance of COVID-19 booster shots vaccination and address worries about safety, and side effects to efficiently reach the target young and low education group with heighten vaccine service quality on the way to build vaccine assurance and lessen hesitancy.